Satire Shows Portrayed by Television and Political Education - Shahzad Husain; Hafiz Ejaz Bashir; Dr. Umair Nadeem (Journal of Political Studies, 2020)
This is a dire need of time to promote Communication and political education in a changing information explosive world. For sustainability, social inclusion is one of the core elements. Television provides information regarding current affairs and entertainment. Viewership of television has increased due to Technological advancement. Developments of political satirical shows are an advanced trend. Satire shows presents political information and education in a very funny way. Satire shows provide beauty to the information and education and people also get entertainment along with political education. The following research aims investigating the nexus of satirical programs popularity among the University going students and to explore the influence of those programs in shaping public judgement. Mimicry and satire shows fulfill purpose of education also. University students are the universe of the study is university students. Survey method is used for data collection of students of selected universities